2015
DOI: 10.1186/s13054-015-0933-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by lipid emulsions in pulmonary inflammation: a randomized controlled trial

Abstract: IntroductionAcute respiratory distress syndrome (ARDS) is a major cause of mortality in intensive care units. As there is rising evidence about immuno-modulatory effects of lipid emulsions required for parenteral nutrition of ARDS patients, we sought to investigate whether infusion of conventional soybean oil (SO)-based or fish oil (FO)-based lipid emulsions rich in either n-6 or n-3 fatty acids, respectively, may influence subsequent pulmonary inflammation.MethodsIn a randomized controlled, single-blinded pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 42 publications
2
26
0
2
Order By: Relevance
“…Moreover, Imai demonstrated that this mediator can be used in combination with the antiviral peramivir, even at late time points in infection [99]. Nevertheless, the efficacy of ω-3 PUFAs at the clinical level is under investigation; for example, Hecker et al described a beneficial effect for a diet regimen with ω-3 PUFAs, describing that the pro-inflammatory cytokine levels decreased after this diet regimen [100]. The suggested positive role in the outcome and prevention of the COVID-19 infection is summarized in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Imai demonstrated that this mediator can be used in combination with the antiviral peramivir, even at late time points in infection [99]. Nevertheless, the efficacy of ω-3 PUFAs at the clinical level is under investigation; for example, Hecker et al described a beneficial effect for a diet regimen with ω-3 PUFAs, describing that the pro-inflammatory cytokine levels decreased after this diet regimen [100]. The suggested positive role in the outcome and prevention of the COVID-19 infection is summarized in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…The anti‐inflammatory and proresolving effects of the EPA‐derived RvE1 have been investigated in several experimental models thus far (Arita et al, ; Hecker et al, ; Keyes et al, ; Seki et al, ). RvE1 exerts its effects by various mechanisms including (1) counter‐regulatory influence on leukocyte functions, (2) phagocytic clearance of apoptotic neutrophils, (3) phenotypic switching of macrophages, and (4) modulation of trafficking and proinflammatory mediator release (Colgan, ; Qu et al, ; Uddin and Levy, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, hyperglycemia contributes to the maintenance of oxidative stress through the generation of RONS (reactive oxygen and nitrogen species) or by altering the redox balance; 4 this creates a vicious self-sustaining cycle known as glucotoxicity. 8 In addition, MMPs are involved in oxidative stress-related cell damage. Glucotoxicity and lipotoxicity may be responsible for the majority of micro-and macrovascular complications induced by diabetes.…”
Section: Introductionmentioning
confidence: 99%